ダイ43ジ ニホン ナンキョク チイキ カンソクタイ カキ コウドウ ホウコク 2001-2002 - 西尾, 文彦; ニシオ, フミヒコ; Nishio, Fumihiko (2013)
P(論文) 第43次隊は総勢60名で構成され,このうち夏隊は20名,越冬隊は40名であった.ほかに夏隊同行者として7名が参加した.南極観測船「しらせ」は,2001年11月14日に晴海埠頭を出港,観測隊本隊は11月28日に航空機で成田を出発し,西オーストラリアのフリーマントルで「しらせ」に乗船した.「しらせ」は12月3日に同地を出発し,海洋観測を実施しつつ12月14日に氷縁へ到着した.12月18日に昭和基地第一便が飛び,12月23日に昭和基地に接岸して氷上輸送,その後の本格輸送が開始された.2002年2月12日の最終便までの間に,第43次越冬成立に必要な物資の輸送と越冬隊員の交代を滞りなく完遂した.また,観測隊ヘリコプターは12月23日に「しらせ」から昭和基地へ移動し,その後2002年2月3日まで氷床内陸域も含めた観測支援作業に従事した.人工地震の観測では内陸に雪上車行動を展開したが,適宜ヘリコプターを利用し空路支援した.基地作業では,昭和基地内の多くの地域で土木・建築作業,基地設備の更新などが行われた.なお,夏隊員のうち4 名は専用観測船「タンガロア号」を利用した観測を実施し,国内出発から帰国まで完全に別行動であった. The activities in the 2001-2002 austral summer of the 43rd Japanese Antarctic Research Expedition (JARE-43) are reported. JARE-43 consisted of 60 personnel including 20 summer and 40 wintering personnel. In addition, 7 observers joined the voyage of R/V Shirase. She left Harumi on Nov. 14 in 2001, and the 56 personel and 7 observers went on boad in Freemantle of Western Australia for Syowa Station, other 4 personel for another ship as mentioned below. R/V Shirase left the ground on Dec. 3 and arrived at the ice edge on Dec. 14, after carrying out marine observations on the cruise. She anchored at Syowa Station on Dec. 23, after the first flight on Dec. 18. All the cargo and fuel necessary for the wintering program of JARE-43 were unloaded and the missions for the summer party were forced to finish by the last flight on Feb. 12 in 2002. The helicopter, chartered by JARE-43, moved to Syowa Station from R/V Shirase on Dec. 23 and supported the observation programs until Feb. 3, including the inland areas of ice sheets. The observation on the Mizuho Ice Plateau for the seismic exploration programs was especially supported by air during the traverse. Constructions with engineering works and facilities update were conducted in the several areas in Syowa Station, and most of them were accomplished, some, however, left for the wintering party. In addition, 4 summer members carried out other marine observations using R/V Tangaroa chartered by JARE-43. departmental bulletin paper